Masculinity and neighbourhood bullying among adolescents in Ibadan, Nigeria- a research note (2019)
Masculinity, as an identity signifier along gender lines, varies from one society to another. The nature, definition, and expression of masculinity (dominance, oppression, violence, and aggression) through social interactions may breed bullying, as found in the Agbowo community of Ibadan, Nigeria. The data for the study were collected through mixed methods and revealed that patriarchal constructed masculinity allows for hegemonic dominance, aggression, oppression, and violent acts that foster bullying among adolescent males in Agbowo. Hence, to address bullying-related problems among adolescents, an understanding of the societal context in which it is carried out is required.